Molecular characterization and protective efficacy of vacuolar protein sorting 29 from Eimeria tenella - Shi, Tuan-yuan; Li, Tian-en; Hao, Yun; Sun, Hong-chao; Fu, Yuan; Yan, Wen-chao; Hao, Li-li (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Vacuolar protein sorting 29 (VPS29) is a core component of the retromer-retriever complex and is essential for recycling numerous cell-surface cargoes from endosomes. However, there are no reports yet on VPS29 of Eimeria spp. Methods Here, we cloned and prokaryotically expressed a partial sequence of Eimeria tenella VPS29 (EtVPS29) with RT-PCR and engineered strain of Escherichia coli respectively. The localization of the VPS29 protein in E. tenella sporozoites was investigated with immunofluorescence (IFA) and overexpression assays. And its protective efficacy against E. tenella infection was investigated in chickens with the animal protection test. Results An EtVPS29 gene fragment with an ORF reading frame of 549 bp was cloned. The band size of the expressed recombinant protein, rEtVPS29, was approximately 39 kDa and was recognized by the chicken anti-E. tenella positive serum. EtVPS29 protein was observed widely distributing in the cytoplasm of E. tenella sporozoites in the IFA and overexpression assays. rEtVPS29 significantly increased average body weight gain and decreased mean lesion score and oocyst output in chickens. The relative weight gain rate in the rEtVPS29-immunized group was 62.9%, which was significantly higher than that in the unimmunized and challenged group (P < 0.05). The percentage of reduced oocyst output in the rEtVPS29 immunized group was 32.2%. The anticoccidial index of the rEtVPS29-immunized group was 144.2. Serum ELISA also showed that rEtVPS29 immunization induced high levels of specific antibodies in chickens. Discussion These results suggest that rEtVPS29 can induce a specific immune response and is a potential candidate for the development of novel vaccines against E. tenella infections in chickens.